Industrial Policies, Manufacturing Sector Development and Macroeconomic Stability in Nigeria - Agri, Eneji Mathias; Kumo, Abubakar Abdullahi; Nshe, Manomi Jeremiah; Gabriel, Adejor Attah (Archives of Business Research, 2023)
The primary focus of this study is on policy determination of industrialization and manufacturing, and the latter’s impact on macroeconomic stability in Nigeria. Since independence, Nigeria’s potential of becoming a global economic giant has been wasted away due to lack of diversification and sluggish manufacturing sector. Government appears to be both the problem and solution to Nigeria’s industrialization. Qualitative and quantitative analysis were applied involving primary and secondary time series data. Questionnaire survey and multiple regression analysis (ARCH) were adopted. The model of manufacturing cannot be complete until political will becomes a major variable/determinant. The survey attributed 32 percent of industrial failure to political factor and lack of political will. This is why Nigeria has not been successful in facilitating industrial transformation, despite the rich endowment. The maximum political commitment to propel industrialization has been absent. Industrialization and manufacturing is state-led through policies and interventions, actualized by private sector investments. Domestic manufacturers invest capital to provide alternative infrastructure for their operations. Consequently, they bear prohibitive costs which result in loss of competitiveness and profitability in the domestic and foreign markets. This is enough dis-incentive to manufacture. It becomes cheaper for them to import from Asia and Europe to repackage and retail. It is a macroeconomic damage that most of Nigeria’s entrepreneurs are merely hawkers of foreign goods for foreign manufacturers, where capital is repatriated in a vicious cycle on daily basis, leaving Nigeria poor and the economy sick. This study recommends strict policy implementation, promotion of home-grown technology by investing in education, skills acquisition, research and development and also bargaining with foreign firms to enable technology transfer. Expansionary monetary and fiscal policies, tariff and exchange rate policies to boost domestic manufacturing, domestic demand and export promotion. The study finally concludes that Nigeria can industrialize with aggressive expansion of domestic markets for goods locally manufactured.